“Oh What a World”: Queer Masculinities, the Musical Construction of a Reparative Cultural Historiography, and the Music of Rufus Wainwright - Schwandt, Kevin C. (Université du Minnesota, 2010)
Throughout his ascendancy in fame and cultural visibility, singer/songwriter and gay pop icon Rufus Wainwright's output has been consistently related, by scholars and critics alike, to camp aesthetics, modes of artistic expression typically understood as emerging from queer communities, particularly certain gay male populations, but ones whose political potential is highly contested. Traditional conceptions of camp, as most famously articulated by Susan Sontag in the 1960s, emphasize style over content, necessarily rendering it politically-disengaged. However, scholars have vehemently challenged conceptions like Sontag's, in order to reclaim camp as a potent means to facilitate queer world-making and a powerful resistance to heteronormativity. I examine Wainwright's image and music in order to theorize a new queer interpretive listening position. Specifically, I draw upon the literary perspective of “reparative reading,” articulated by Eve Kosofsky Sedgwick in opposition to what she describes as “paranoid reading,” to propose a uniquely queer approach to musical and cultural historiography, exemplified by Wainwright's music. Much of the current queer musicology focuses on lost histories, systematic marginalization, and the commoditization of queer identities. While such approaches have produced important insights, thorough examination of the relationships between queer cultural products and their queer reception has proven elusive. This project suggests a unique approach to understanding the musical construction of a specific kind of queer masculinity, one which combines authorial creation with reparative conceptions of reception, in order to theorize a uniquely gay male interpretive position. When viewed through a theoretical lens combining politically-potent conceptions of camp performativity with a reparative reading position, Wainwright's music strikingly enacts Philip Brett's call to claim, not historical evidence, but the right of interpretation, emerging as an act of resistance via the reclamation and consolidation of a queer interpretive authority. In this way, Wainwright articulates both a rupture in the history of queer masculinity and a powerful means of resistance to the often-exclusionary relationships between literary, musical, and artistic objects and the heteronormative cultural systems in which they are created.
Keywords: Communication and the arts; Gay history; Gay rights; Historiography; Masculinities; Popular culture; Queer; Reparative reading; Rufus; Social sciences; Wainwright

The Songs of Violet Archer: Tracing the Evolution of One of Canada's Most Prominent Composers - Dauphinais, Paul (Université de Boston, 2016)
In this study, four sets of songs composed by Violet Archer are examined, all of which were written at different points in her career. Archer studied with Paul Hindemith in 1948 – 49, and his teachings had a tremendous impact on the young composer. The first set of songs to be analyzed, Moon Songs, was written before her time with Hindemith, and will provide a baseline from which her later, post-Hindemith, works can be compared. Following her studies with Hindemith, Archer wrote three songs, “Cradle Song,” “April Weather,” and “First Snow,” all of which show evidence of Hindemith’s influence. Her later, more mature works, Northern Landscape and Caleidoscopio Quatro, demonstrate a refined compositional technique; one in which Archer has created her own style, while maintaining aspects of the approach taught by Hindemith at Yale. This study will elaborate on the aspects of Archer’s music that evolved throughout her compositional career.
Keywords: Archer; Communication and the arts; Hindemith; Music analysis; Paul; Social sciences; Violet